Processing Dante’s Commedia: From Sanguineti’s Edition to Digital Tools - Spadini, Elena (Enthalten in:RIDE;Köln : Institut für Dokumentologie und Editorik, [2014]-;Online-Ressource)
Abstract: The Commedia project aims to investigate the manuscript transmission of the poem, using Sanguineti's previous edition and checking the validity of his stemma with computer methods. Full transcriptions of the seven selected witnesses are provided alongside the corresponding facsimiles. The end results of the collation and phylogenetic analysis differ from Sanguineti's edition and reshape the stemma. No new critical text is provided. The edition is easy to navigate and high quality editorial materials are available. A metrical markup enriches the text and the integrated VBase tool allows the user to retrieve variants in different witnesses and parts of the poem
10.18716/ride.a.3.2
Keywords: 14th century; collation; critical edition; dante; facsimile; italian; manuscript transmission; metrical markup; phylogenetic analysis; tei; transcription; variant